Hemispheric Asymmetry in the Hierarchical Perception of Music and Speech. - Rosenthal, Matthew A. (Psychological Bulletin, 2016)
The perception of music and speech involves a higher level, cognitive mechanism that allows listeners to form expectations for future music and speech events. This article comprehensively reviews studies on hemispheric differences in the formation of melodic and harmonic expectations in music and selectively reviews studies on hemispheric differences in the formation of syntactic and semantic expectations in speech. On the basis of this review, it is concluded that the higher level mechanism flexibly lateralizes music processing to either hemisphere depending on the expectation generated by a given musical context. When a context generates in the listener an expectation whose elements are sequentially ordered over time, higher level processing is dominant in the left hemisphere. When a context generates in the listener an expectation whose elements are not sequentially ordered over time, higher level processing is dominant in the right hemisphere. This article concludes with a spreading activation model that describes expectations for music and speech in terms of shared temporal and nontemporal representations.